God says ‘gay rights’: queering Christian theology in the Good Omens fandom - Romanzi, Valentina (Culture and religion, 2021)
In this essay I investigate how fandom discourse comments on, adapts, and reinvents existing theology. Using a selection of Good Omens fan works and ‘meta’ online posts as a case study, I argue that they welcome instances of queer theology while moving forward issues pertaining to the LGBTQ+ liberation movement. In expanding and altering the source material, fan fiction authors retrieve Biblical myths to legitimise the inclusion of queer individuals in Christian theology – the stated intent of the LGBTQ+ liberation movement. Additionally, they often offer a revisited, inclusive depiction of God as the ‘ur-ally’, framing them/her/him as an ‘ineffable’ figure made of encompassing and all-accepting love. Moreover, Good Omens fan fiction situates the binary forces of Heaven and Hell as the antagonists to the much more nuanced and queer-coded protagonists, who embrace humanity and reject notions of hard-set dichotomies. This celebration of queerness as opposed to strict dualisms fits into the purported goals of queer theology, which has no direct interest in finding a place for queer people within the existing Christian tradition, but rather works towards the dismantling of harmful dualities.